GOOGLE SITES-BASED LEARNING MEDIA IN NATURAL SCIENCE LESSONS IN ELEMENTARY SCHOOL : A LITERATURE STUDY - Rahindra, Rahadian; Maksum, Arifin; Aruwiyantoko, Anggit (PROGRES PENDIDIKAN, 2025)
The writing of this article aims to review various journal articles on the development of learning media based on Google Sites in learning Natural Sciences in elementary schools. The method used in writing the article is a literature study of articles that have been published in the period between 2020 and 2025. The results of the study state that there is feasibility in learning science at the elementary school level using Google Sites-based learning media. Validity assessments from media experts and material experts are on average in the "very valid" category (above 90%), and teacher and learner responses indicate a high level of practicality and effectiveness. In addition, there were several articles that had a significant increase in learning outcomes as indicated by N-Gain values in moderate to high levels. Google Sites is proven as a learning media that can successfully improve the quality of science learning in elementary schools.